A Comprehensive Review About the Use of Monoclonal Antibodies in Cancer Therapy - Angel Justiz-Vaillant; Bijay Raj Pandit; Chandrashekhar Unakal; Sehlule Vuma; Patrick Eberechi Akpaka (Antibodies, 2025)
Monoclonal antibodies (mAbs) targeting various pathways in cancer therapy play crucial roles in enhancing the immune system’s ability to recognise and eliminate tumour cells. These therapies are designed to either block inhibitory immune checkpoint pathways or to target specific tumour cell markers for direct destruction. Additionally, mAbs can modulate the tumour microenvironment, enhance antibody-dependent cellular cytotoxicity, and inhibit angiogenesis, further amplifying their therapeutic impact. Below is a summary of monoclonal antibodies targeting key pathways, along with their indications and mechanisms of action, which are reviewed based on therapeutic mechanisms.